2015
DOI: 10.1097/gme.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor and depression symptoms may be associated with different sleep disturbance patterns in postmenopausal women

Abstract: VMS and depression symptoms are associated with different patterns of sleep disturbance. Although both symptoms are related to sleep quality, daytime functioning, and daytime well-being, depression is uniquely associated with difficulty falling asleep and waking up earlier than desired, whereas VMS are related to frequent awakenings during sleep. The findings are limited by the cross-sectional design and relatively small sample size of the study. Recommendations for future research are discussed to guide this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
0
29
2
1
Order By: Relevance
“…Menopausal transition has been documented as an important hallmark for increased risk for sleep disturbances [5][6][7]. Furthermore, concurrent vasomotor symptoms add to the risk [9][10][11]24]. Thus, the existence of vasomotor symptoms might differentiate the distinct menopausal phenotypes, and hence identify those at risk for developing sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Menopausal transition has been documented as an important hallmark for increased risk for sleep disturbances [5][6][7]. Furthermore, concurrent vasomotor symptoms add to the risk [9][10][11]24]. Thus, the existence of vasomotor symptoms might differentiate the distinct menopausal phenotypes, and hence identify those at risk for developing sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other causes may be psychological factors due to depression, emotional problems, or physical disturbances. [14][15][16][17][18][19] In fact, we observed a large number of patients with arthropathy that may limit their physical activity and worsen their quality of life. Moreover, our data showed that not all patients performed regular physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…14 Regardless of the mechanism, we found a high number of patients with depression, which decreases the quality of life. [14][15][16][17][18] Fonseca et al 11 observed that $ 68% of the patients were overweight or obese during the climacterium. According to Lynch et al, 20 the excess weight may affect the overall health and the quality of life of women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of L. Kolesnikova et al (2017) have shown that perimenopausal women have more frequency of the difficulty falling asleep and postmenopausal ones have more the number of nocturnal awakenings [32]. Various works were devoted to the role of vasomotor symptoms in menopausal women in the pathogenesis of insomnia [24,46]. The presence of vasomotor symptoms in postmenopause makes the risk of night awakenings 1.85 times higher [46].…”
Section: Menopause As a Risk Factor Of Sleep Disordersmentioning
confidence: 99%